2007
DOI: 10.1159/000113149
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Platelet-Activating Factor Receptor: A Novel Prognosticator in Patients with Hepatocellular Carcinoma following Hepatectomy

Abstract: Backgrounds and Aims: Platelet-activating factor (PAF, 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) is a phospholipid mediator and acts by binding to a specific G-protein-coupled receptor. Though various functions of PAF have been associated with tumor activities, the mechanism of PAF-PAF receptor signaling in the development of hepatocellular carcinoma (HCC) remains to be elucidated. Methods: In this study, PAF receptor (PAFR) expression was examined in hepatoma cell lines (Huh7, PLC/PRF/5 and HepG2) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…Weak PAFR expression was also noted in epithelial cells in 6 cases of gastritis [Giaginis et al, unpublished data]. In accordance with our findings, an immunohistochemical study conducted on 60 hepatocellular carcinoma patients revealed significant association between low PAFR expression and poor tumor [41]. Moreover, this study indicated that multiple recurrences and distant metastases were more often observed in patients presenting low compared to those with high PAFR expression [41].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Weak PAFR expression was also noted in epithelial cells in 6 cases of gastritis [Giaginis et al, unpublished data]. In accordance with our findings, an immunohistochemical study conducted on 60 hepatocellular carcinoma patients revealed significant association between low PAFR expression and poor tumor [41]. Moreover, this study indicated that multiple recurrences and distant metastases were more often observed in patients presenting low compared to those with high PAFR expression [41].…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with our findings, an immunohistochemical study conducted on 60 hepatocellular carcinoma patients revealed significant association between low PAFR expression and poor tumor [41]. Moreover, this study indicated that multiple recurrences and distant metastases were more often observed in patients presenting low compared to those with high PAFR expression [41]. Another immunohistochemical study revealed that PAFR expression was significantly increased in ovarian cancer patients compared to benign ovarian tissue specimens, being varied across different histological subtypes of the ovarian cancer [40].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, studies have found that crosstalk between protease-activated receptor 1 and PAFR regulates melanoma metastasis (14) and PAFR activation augments the growth and metastasis of lung cancer (15). However, some studies have found that lower expression of PAFR correlats with poor differentiation and a poor prognosis in patients with hepatocellular carcinoma after hepatectomy (16), and PAFR expression is negative associated with histopathological stage and grade and patient survival in gastric adenocarcinoma (9). In prostate cancer cells, Jan and Chao (17) found that a specific PAFR antagonist inhibits prostate cancer cell growth, but the function of PAFR in the progression of prostate cancer cells and the underlying molecular mechanisms are still not very clear.…”
Section: Discussionmentioning
confidence: 99%